Systematic study of the influence of the molecular structure of fluorinated ionic liquids on the solubilization of atmospheric gases using a soft-SAFT based approach - Ferreira, Margarida L. (2022)
FCT/ MCTES (Portugal) through grant SFRH/BD/130965/2017 (M. L. Ferreira) and Investigador FCT 2014 ( IF/00190/2014 to A. B. Pereiro and IF/00210/2014 to J. M. M. Araújo), and projects PTDC/EQU-EQU/29737/2017, PTDC/QEQ-FTT/3289/2014 and IF/00210/2014/CP1244/CT0003. This work was also supported by the Associate Laboratory for Green Chemistry – LAQV, which is financed by national funds from FCT / MCTES ( UID/QUI/50006/2019 ). Additional financial support has been provided by Khalifa University of Science and Technology through projects RCII-2018-24 (CeCaS Center) and RCII-2019-007 (RICH Center), as well as projects 2018-LC-01 and 2019-URL-IR1rQ-011 from Obra Social “La Caixa” .